2009
DOI: 10.1097/inf.0b013e3181aa6c3e
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus and Other Respiratory Viral Infections in Children Attending a Day Care Center

Abstract: Human metapneumovirus (hMPV) is an important cause of acute respiratory infections (ARI). We studied 335 ARI episodes in 74 children<5 years of age attending a day care center during a 1-year period to detect the presence of hMPV and other viruses. Seven (9.5%) children were infected by hMPV and this virus accounted for 2.1% of the ARI episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In Mexico, the first study in which the presence of this virus was determined was published in 2005 [40]. Subsequently, other Mexican studies demonstrated its importance in the child population [16;4142]. Studies such as that of Diaz et al [16] demonstrated that HMPV was mostly associated with severe acute respiratory infections instead of mild and moderate infections.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, the first study in which the presence of this virus was determined was published in 2005 [40]. Subsequently, other Mexican studies demonstrated its importance in the child population [16;4142]. Studies such as that of Diaz et al [16] demonstrated that HMPV was mostly associated with severe acute respiratory infections instead of mild and moderate infections.…”
Section: Discussionmentioning
confidence: 99%
“…This virus recently has been identified and has been associated with ARI in children and adults [ 25 , 26 ]. In Mexico, a few studies on the prevalence of hMPV have been conducted in the pediatric population, and the frequency has been reported to range from 6% to 20% [ 27 - 29 ]. In this study, this virus was detected in 22% of children, a value that is very similar to what has been reported in Mexico [ 28 , 29 ] and elsewhere (reviewed in [ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, a few studies on the prevalence of hMPV have been conducted in the pediatric population, and the frequency has been reported to range from 6% to 20% [ 27 - 29 ]. In this study, this virus was detected in 22% of children, a value that is very similar to what has been reported in Mexico [ 28 , 29 ] and elsewhere (reviewed in [ 30 ]). Furthermore, our results contrast with those of other studies in which RSV ranks as the most frequent virus in the pediatric population with ARI [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Statistical analysis Comparison of patient groups was carried out using SPSS 14.0 for Windows. Categorical variables were compared using the chi-square or Fisher's exact test, as appropriate.…”
Section: Rsv Detectionmentioning
confidence: 99%